The Influence of the STEAM-Based Problem Based Learning Model on the Science Process Skills of Madrasah Aliyah Negeri 3 Medan Students - Nikma Hanna Mariana Hutabarat; Sutri Novika; Rofiqoh Hasan Harahap; Juliandi Siregar (ASIAN: Indonesian Journal of Learning Development and Innovation, 2024)
The aim of this research is to find out the comparative influence of the PBL model and the STEAM-based PBL model on improving the science process skills of Madrasah Aliyah Negeri 3 Medan students. By applying the STEAM-based PBL model in learning activities, students' science process skills are formed, thus giving students a new learning style in participating in physics learning. The research was conducted to see the effect of the STEAM-based PBL model on improving the science process skills of Madrasah Aliyah Negeri 3 Medan students. This research used a quasi-experiment, the sample for this research was taken using random sampling technique for class XI MIPA which consisted of an experimental class and a control class. The t-test obtained with tcount > ttable (3.75 > 0.721) with a significance level of α=5% (0.05). So H0 is rejected. It can be concluded that on average the experimental class is better, and the STEAM-based Problem Based Learning model has an influence on students' science process skills with a sufficient index category (70.59).